Anticancer effects of dihydromyricetin on the proliferation, migration, apoptosis and in vivo tumorigenicity of human hepatocellular carcinoma Hep3B cells - Lianggui Jiang; Wen-Chu Ye; Zuobiao Li; Yongguang Yang; Wei Dai; Mingyi Li (BMC, 2021)
Abstract Background Hepatocellular carcinoma (HCC) represents a serious public health problem worldwide and has high morbidity and mortality. Dihydromyricetin (DHM) exhibits anticancer effect on a variety of malignancies, but its anticancer function of DHM in HCC has been unclear. The aim of this study was designed to investigate the anticancer effect of DHM on cell apoptosis, proliferation, migration and invasion of hepatoma carcinoma cells. Methods Cultured Hep3B cells were treated with different DHM concentrations, followed by cell apoptosis, proliferation, migration and invasion were examined by CCK-8, colony formation assay, wound healing, Transwell and flow cytometry, respectively. The mRNA and protein expression of BCL-2, Cleaved-caspase 3, Cleaved-caspase 9, BAK, BAX and BAD were validated by western blot. Results DHM markedly suppressed proliferation, migration, invasion and facilitated apoptosis in Hep3B cells. Mechanistically, DHM significantly downregulated the Bcl-2 expression, and upregulated the mRNA and protein levels of Cleaved-Caspase 3, Cleaved- Caspase 9, Bak, Bax and Bad. Furthermore, in the nude mice tumorigenic model, DHM treatment greatly decreased the weight of the HCC cancers compared to the weights in control and NDP group. Conclusions DHM could suppress cell proliferation, migration, invasion, and facilitated apoptosis in Hep3B cells. These findings could provide novel insights to develop potential therapeutic strategy for the clinical treatment of HCC.